Harvesting of microalgae botryococcus sp. Through phycoremediation of bathroom greywater - Atiku, Hauwa Maijidda (2016)
Malaysia has been experiencing water pollution crisis over a decade and one of the causes is direct discharge of greywater into the drains. Therefore, phycoremediation of greywater especially from bathroom sources with microalgae is proposed. The objectives of this research are to measure the efficiency of Botryococcus sp. in assimilating pollutant load, to optimize the flocculation process and investigate the interactive effects of experimental factors through Response Surface Methodology (RSM) design expert software. Botryococcus sp. was inoculated in bathroom greywater with 4.5 x 106 cell/mL for phycoremediation process. Microalgae Botryococcus sp. grown in bathroom greywater from House A, House B and House C and tested for reduction of pollutant. Results shown that the highest reduction for COD was at House A with 87 %, BOD5 was reduced to 96 % at House C which is the highest reduction, NH4+ highest was reduced at House A with 98 % and PO43- highest reduction occurred at House C with 88 % on the 21st day of phycoremediation respectively. Whereas, Moringa oleifera and Strychnos poatatorum were used in harvesting Botryococcus sp. in bathroom greywater via flocculation technique. A central composite design, which is the standard design of response surface methodology (RSM), was used to evaluate the effects and interactions of three factors, i.e. coagulant dosage, settling time and pH on the harvesting efficiency. Lastly, the biomass recovery was conducted via optical density to calculate the biomass recovery for M. oleifera and S. potatorum. The optimal conditions obtained from the compromise of one desirable responses, turbidity was at coagulant dosage of 10 mg /L, settling time of 120 min, and pH 9 respectively. The biomass recovery percentage for Botryococcus sp. by using Moringa oleifera and Strychnos potatorum were 97 % and 81 % accordingly. Therefore, this study proved that the cultivation of microalgae in bathroom greywater was successful in reducing the amount of pollutant tested in this research.